Extracellular vesicles as a novel therapeutic tool for cell‐free regenerative medicine in oral rehabilitation. (27th September 2019) - Lv, Longwei; Sheng, Chunhui; Zhou, Yongsheng
Abstract: Oral maxillofacial defects may always lead to complicated hard and soft tissue loss, including bone, nerve, blood vessels, teeth and skin, which are difficult to restore and severely influence the life quality of patients. Extracellular vesicles (EVs), including exosomes, microvesicles and apoptotic bodies, are emerging as potential solutions for complex tissue regeneration through cell‐free therapies. In this review, we highlight the functional roles of EVs in the regenerative medicine for oral maxillofacial rehabilitation, specifically bone, skin, blood vessels, peripheral nerve and tooth‐related tissue regeneration. Publications were reviewed by two researchers independently basing on three databases (PubMed, MEDLINE and Web of Science), until 31 December 2018. Basing on current researches, we classified the origin of EVs for regenerative medicine into four categories: related cells in the regenerative niche, mesenchymal stem cells, immune cells and body fluids. The secretome of different cells are distinct, while the same cells secrete different EVs under varied conditions; therefore, the content profiles of EVs and regulatory mechanisms on target cells are compared and emphasised. By unravelling the regulatory mechanisms of EVs in tissue regeneration, modified cells and tailored EVs with specific target may be produced for precision medicine with high efficacy.